1992
DOI: 10.1111/j.1095-8649.1992.tb02679.x
|View full text |Cite
|
Sign up to set email alerts
|

The periodicity of primary increment formation in the otoliths of Arctic charr Salvelinus alpinus (L.)

Abstract: The role of environmental factors in the regulation of sub-annual increment formation in fish otoliths appears to differ markedly between species. To examine the periodicity of primary increment formation in the otoliths of 0 + Arctic charr, Salvelinus alpinus (L.), and the effects of temperature, and photoperiod on their formation, fish were held under controlled environmental conditions. Primary growth increments were found in the otoliths of fish held at constant temperature (18" C) and at ambient temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The investigator must not be too hasty rejecting the use of increments to provide fish ages solely on the basis of a significance test without noting the magnitude of the deviation from daily. Adams et al (1992), while investigating increments in Arctic charr, found that increments were significantly not daily; however, the number of increments deposited after 100 days differed from 100 by only 3%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigator must not be too hasty rejecting the use of increments to provide fish ages solely on the basis of a significance test without noting the magnitude of the deviation from daily. Adams et al (1992), while investigating increments in Arctic charr, found that increments were significantly not daily; however, the number of increments deposited after 100 days differed from 100 by only 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Chinook salmon O. tshawytscha (Walbaum) did continue daily increment formation at 4 C (Neilson & Geen, 1982) with only reduced increment thickness. Adams et al (1992) have validated daily increments in Arctic charr held at ambient temperatures (4 to 18 C) with a 2 to 3 C daily fluctuation. In our study, otolith increment deposition was observed under all experimental conditions (1 to 7 C) and was daily among charr reared at 'higher' temperatures (5 to 7 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth increments are deposited daily at hatch and enumerating the increments has been used to estimate hatch dates reliably in many species including salmonids Stevenson & Campana, 1992;Tsukamoto et al, 1989;Yamamoto et al, 1997). Although cold temperatures typically reduce increment widths, increments have been successfully used to determine fish ages in salmonids subject to near-freezing temperatures (Adams et al, 1992;Nielsen & Green, 1982;. This method readily applies to young-of-the-year (YOY) individuals collected when field sampling has become feasible, and the individuals have become large enough for efficient capture during a snow-free period.…”
mentioning
confidence: 99%
“…The field component of this study was preceded by a hatchery component using individuals with known hatch date ranges to validate age estimates and evaluate precision of age assignments among independent readers. Although otolith microstructural analysis has been applied successfully to infer hatch timing of both study species (Tsukamoto et al, 1989;Yamamoto et al, 1997), the age validation was deemed important because salmonids may deposit sub-daily increments on otoliths (Adams et al, 1992;Stevenson & Campana, 1992).…”
mentioning
confidence: 99%